2020
DOI: 10.5811/cpcem.2020.7.48358
|View full text |Cite
|
Sign up to set email alerts
|

Morel-Lavallée Lesion Following a Low-speed Injury: A Case Report

Abstract: Introduction: Soft tissue injuries are a common presenting complaint seen in the emergency department following trauma. However, internal degloving injuries are not commonly seen by the emergency provider. Case Report: A 57-year-old male presented with right lower extremity pain, bruising, and swelling after a low-speed bicycle accident five days prior. Physical examination revealed an edematous and ecchymotic right lower extremity extending from the mid-thigh distally. Computed tomography of the thigh demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nine case reports/series, 1,[4][5][6][7][8][9][10][11] seven retrospective studies, 2,[12][13][14][15][16][17] three prospective studies, [18][19][20] eight review articles, 3,[21][22][23][24][25][26][27] and one systematic review 28 fulfilled our inclusion criteria. The characteristics of the prospective and retrospective studies included in this review pertaining to the ML lesion, the mechanism of injury, treatment received and its outcome are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine case reports/series, 1,[4][5][6][7][8][9][10][11] seven retrospective studies, 2,[12][13][14][15][16][17] three prospective studies, [18][19][20] eight review articles, 3,[21][22][23][24][25][26][27] and one systematic review 28 fulfilled our inclusion criteria. The characteristics of the prospective and retrospective studies included in this review pertaining to the ML lesion, the mechanism of injury, treatment received and its outcome are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…12 The studies included in this review concluded that MRI is the diagnostic imaging modality of choice in the assessment of ML lesions, due to its high contrast resolution, multiplanar image acquisition and enhanced anatomic details. 10,26 The magnetic properties of blood breakdown products are an essential factor that determine the MRI appearance of ML lesions. The acute ML lesion (Figure 3) appears hypointense on T1-weighted (T1-WI) images and hyperintense on T2-weighted (T2-WI) images due to presence of blood within the lesion.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…DSTIs may encompass a wide variety of traumatic forces, each presenting with a relatively unique challenge in terms of tissue damage and subsequent management. High-energy traumas, usually stemming from MVAs and industrial accidents, can subject the body to extremely high-impact forces, resulting in DSTIs that may span large body regions and may have additional fractures or internal injuries [3]. Crush injuries, also seen in industrial accidents, or falls, generate forces that separate skin and soft tissue from underlying structures [1].…”
Section: Introductionmentioning
confidence: 99%